Pengembangan Bahan Ajar Sastra Anak Berbasis Kearifan Lokal bagi Murid Sekolah Dasar - Usman Usman; Sakaria Sakaria (Jurusan Tadris Bahasa Indonesia, 2020)
This study aims to develop valid, practical, and effective literary teaching materials based on character education in elementary schools. The study used the Borg and Gall development model which was then adapted into four stages, namely: (1) pre-development stage (planning), (2) product development stage, (3) product feasibility test stage, and (4) post-development stage. This study involved fourth-grade elementary school students. The study results showed that the development of children's literature teaching materials is important. The teaching materials were declared feasible, both according to material and media experts and students. The teaching materials were proven to be effective and can be used independently.Penelitian ini bertujuan untuk mengembangkan bahan ajar sastra yang valid, praktis, dan efektif berbasis pendidikan karakter di sekolah dasar. Penelitian menggunakan model pengembangan Borg dan Gall yang kemudian diadaptasi menjadi empat tahap, yaitu: (1) tahap prapengembangan (perencanaan), (2) tahap pengembangan produk, (3) tahap uji kelayakan produk, dan (4) tahap pascapengembangan. Penelitian ini melibatkan siswa SD kelas IV. Hasil penelitian menunjukkan bahwa pengembangan bahan ajar sastra anak penting dilakukan. Bahan ajar dinyatakan layak, baik menurut ahli materi dan media maupun peserta didik. Bahan ajar terbukti efektif dan dapat digunakan secara mandiri.